2011
DOI: 10.1111/j.1528-1167.2011.03047.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparability of the new antiepileptic drugs in refractory partial epilepsy: A systematic review and meta-analysis

Abstract: SUMMARYPurpose: Evaluate the clinical comparability of new antiepileptic drugs (AEDs) in partial refractory epilepsy. Methods: Systematic review of randomized trials (RCTs) comparing a new AED (add-on treatment) with placebo or another AED. Primary outcomes: responder ( ‡50% seizure reduction) and withdrawal (tolerability) rates. Pooled estimates of odds ratios (ORs) and number needed treat/harm (NNT/NNH) taking into account baseline risk were derived by random-effects meta-analysis. Adjusted frequentist indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 43 publications
5
82
1
3
Order By: Relevance
“…Other authors, however, have presented similar findings. 12,13 In our opinion, the most noteworthy finding from this study is that it does not identify fewer adverse events for new drugs than for classic drugs. It does show different ranges of adverse events for each of the two drug types, and this finding is consistent with results from other studies.…”
Section: Aedmentioning
confidence: 82%
“…Other authors, however, have presented similar findings. 12,13 In our opinion, the most noteworthy finding from this study is that it does not identify fewer adverse events for new drugs than for classic drugs. It does show different ranges of adverse events for each of the two drug types, and this finding is consistent with results from other studies.…”
Section: Aedmentioning
confidence: 82%
“…AEDs have a better effect than placebo in the treatment of partial-onset epilepsy [28]. The analysis by Gao et al [16].…”
Section: Discussionmentioning
confidence: 98%
“…The efficacy of newer antiepileptic drugs has been proven by the results of several randomized, double-blind, placebo-controlled, add-on trials carried out in patients with drug-resistant epilepsy and confirmed by systematic reviews and meta-analyses [27][28][29][30][31][32][33][34][35]. In these studies, the increased chance of a 50% or greater reduction in seizure frequency compared with placebo ranged from 2.0 (lacosamide) to 4.3 (topiramate) ( Table 4), but the probability of seizure freedom was very low (pooled estimate 2%) as no greater than 6.5% of cases (levetiracetam) were reported to be seizure-free during the course of the study.…”
Section: Randomized Clinical Trials With Newer Antiepileptic Drugsmentioning
confidence: 99%
“…In these trials, common adverse events were reported most frequently among patients receiving active treatment (Table 5). Discontinuation rates for adverse events ranged from 3 to 26% of cases depending on drug and daily dose [27] (also see Table 4). In addition, specific adverse events are predominant with some compounds, including psychosis (vigabatrin), depressive symptoms (zonisamide), affective disorders (levetiracetam) and cognitive impairment (topiramate, retigabine and zonisamide).…”
Section: Randomized Clinical Trials With Newer Antiepileptic Drugsmentioning
confidence: 99%